A Comparison of Clinical and Radiological Outcomes between Open and Minimally Invasive Transforaminal Lumbar Interbody Fusion - Waqas Noor Chughtai, Muhammad Adeel Razzaque, Tanveer Ahmad, Manqoosh Ur Rehman, Azhar Rashid, Amjad Maqsood (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the clinical, radiological and functional outcomes of patients between open TLIF and minimally invasive TLIF techniques. Study Design: Prospective cohort study Place and duration: Study was conducted at department of neurosurgery Bakhtawar Amin Hospital, Multan from August 2021 to July 2022 in duration of one year. Methodology: A total of 94 patients planned for transforaminal lumbar interbody fusion (TLIF) were enrolled in study. Main variables of study were intra operative blood loss, duration of surgery, VAS score, ODI index and functional score. SPSS version 24 was used for data analysis, t-test and chi square test were applied to see association among variables. P value less than or equal 0.05 was considered as significant. Results: Oswestry disability index readings were 35.16±2.18 and 5.12±0.61 in O-TLIF and MIS-TLIF groups respectively at 3 weeks after surgery. The differences were statistically insignificant, (p>0.050). Physical component summary of both the groups at different time intervals as shown better outcomes in MIS-TLIF group, no difference was found to be statistically significant except at 6 week. Mental component summary in both the groups was almost equal, (p>0.050). Implications: There was no local study on comparison of open and minimally invasive technique for TLIF, our study will fulfill the local reference gap and help the surgeons for choice of better management technique in future. Conclusion: Minimally invasive surgery TLIF technique is better in immediate benefits as soft tissue injury and iatrogenic injury which is associated with better post operative pain functional recovery time. So, minimal invasive interbody fusion is a safe and reliable option for short term (blood loss, post operative pain) and long term outcomes like functional recovery. Keywords: Interbody fusion, VAS score, SF-36, ODI index, TLIF Technique